Early enteral nutrition in acute pancreatitis - how beneficial is it? - Venkat, Shruthikamal; Subramaniam, Rajesh; Raveendran, Vijai (International Surgery Journal, 2021)
Background: Acute pancreatitis is an inflammatory disease of pancreas and is one of the leading cause of acute abdomen requiring hospital admission. Nutritional support plays a crucial role in this hypercatabolic state in not only providing calories but also in preventing complications and decreasing recovery time. Methods: This prospective study was done among 120 patients with acute moderate and severe pancreatitis who got admitted in department of general surgery at Saveetha Medical College and Hospital, Chennai, Tamil Nadu, India between 2018 and 2019. Results: 67 (55.8%) patients were in early enteral and 53 (44.2%) were in parenteral/delayed enteral group. Maximum number of patients were in 30-40 years age group. The mean of patient age was 40.33. Mean duration of hospital stay in enteral group was 7.06 and in parenteral/delayed enteral group it was 14.09 (p<0.001). Mean pain score in enteral group was 2.69 and in parenteral group it was 6.51 (p<0.001). Conclusions: There was significant (p<0.001) decrease in hospital stay duration and pain score in early enteral group compared to parenteral/delayed enteral group. Infections related to feeding route was found high in parenteral group. No significant difference found in complications of acute pancreatitis. Hence early enteral feeding is more beneficial in terms of shortened hospital stay, decreased pain score leading to reduction in usage of analgesics and reducing the recovery time and less nutrition related complications in management of acute moderate and severe pancreatitis.